The Review of Leadership in Perspectives of Educational Management (International Journal of Innovative Research in Engineering & Management, 2023)
This article analyses the perspectives of  educational management studies and the importance of  leadership as an area of study. The article emphasizes the  importance of research evaluation as well as future  research directions identifying them as a method to view  past progress current issues and future recommendations  to effective educational leadership and management. The  study looked at key influences in this direction such as  educational administration and research leadership, lead  and administer education as a humane and ethical  endeavour rather than a solitary scientific activity; and  analytical resources available to the investigation, evaluate different philosophical and analytical methods in  accordance with an agreed set of academic steps for  scholars policymakers and practitioners; the potential  impact of the maturity of a future generation of  researchers on the primacy of educational administration, and current situation. The field of education leadership  and administration has made remarkable progress. In  future work by scholars on this particular topic the  analysis performed in this paper will provide practical  responses from intellectuals and their organizations as  well as policy makers. Policy makers and education  professionals key stakeholders in the fields of information  leadership and academic management.
Keywords: Academic Leadership; Education Administration; Educational Leadership; Education Management; Leadership